First Peoples of Canada : Masterworks from the Canadian Museum of Civilization - Pilon, J.-L. (Jean-Luc); Yellowhorn, Eldon, 1956-; Dyck, Ian G.; Prince, Nicholette, 1964-; Laforet, Andrea Lynne, 1948- (Book collections on Project MUSE., 2013)
This beautifully designed, full-colour book presents a collection of 150 archaeological and ethnographic objects produced by Canada's First Peoples - including some that are roughly 12,000 years old - that represent spectacular expressions of creativity and ingenuity.